IMPROVEMENT OF DRILLING AND COMPLETION MATERIAL WITHDRAWAL SYSTEM AT PT. CHEPACINDO THROUGH JUST IN TIME APPROVAL PROCESS (The Indonesian Journal of Business Administration, 2021)
Rig operation is critical activity in upstream oil production. To support 24/7 operation the company operates 24-hour material Go Down and Warehouse. There is redundancy in operation of these two facilities. The cost of this redundancy is contributed from manpower, transportation, heavy equipment, and utility cost with total per year around 3.4 billion rupiah.To identify the existing process and connection between the factors, swim lane diagram was used, and then the root cause was investigated using current reality tree. It was found that the operation of D&C Go Down during office hours and the delay purchase approval have caused this redundancy.By evaluating the existing process the redundancy process can be eliminated by using just in time approval process. The combinations of alternatives were assessed and selected using the Kepner – Tregoe method. In the new procedure, D&C Go Down can be closed during office hour.Implementation of this new procedure will require new IT tools, delegation of Authority of purchase approver and socialization of new procedure to all stakeholders. With the implementation of selected solution, redundancy of D&C Go Down and Warehouse can be eliminated.Keywords: Rig operation, Rig material distribution, Material buffer storage, Just in Time Approval